2020
DOI: 10.3390/pathogens9050387
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis Uptakes Carbohydrate Source from Host Glycoproteins by N-glycans Degradation System for Optimal Survival and Full Virulence during Infection

Abstract: Infection with the epidemic virulent strain of Streptococcus suis serotype 2 (SS2) can cause septicemia in swine and humans, leading to pneumonia, meningitis and even cytokine storm of Streptococcal toxic shock-like syndrome. Despite some progress concerning the contribution of bacterial adhesion, biofilm, toxicity and stress response to the SS2 systemic infection, the precise mechanism underlying bacterial survival and growth within the host bloodstream remains elusive. Here, we reported the SS2 virulent stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…To survive and even proliferate in host blood, S. suis must mainly overcome the innate immunity and nutritional limitations in this host compartment [24]. Ma et al [31] found that S. suis serotype 2 virulent strains with higher proliferative ability in swine serum than low-virulent strains, possess a >20 kb endoSS-related insertion region. Further analyses identified a complete N-glycans' degradation system encoded within this insertion region.…”
mentioning
confidence: 99%
“…To survive and even proliferate in host blood, S. suis must mainly overcome the innate immunity and nutritional limitations in this host compartment [24]. Ma et al [31] found that S. suis serotype 2 virulent strains with higher proliferative ability in swine serum than low-virulent strains, possess a >20 kb endoSS-related insertion region. Further analyses identified a complete N-glycans' degradation system encoded within this insertion region.…”
mentioning
confidence: 99%
“…However, ST25 (CC29) and ST28 (CC28), accounting for larger proportions of SS2 strains in North American, present less virulence potentials in animal model (Athey et al, 2015; Fittipaldi et al, 2011). In accordance, ST28 strains in China are also regard as representive avirulent strains (Guo et al, 2020; Ma et al, 2020; Wang et al, 2017). Those reports suggested that CC28 and CC29 SS2, which are phylogenetically distinct from CC1 SS2, are the pool of strains with lower virulence levels.…”
Section: Discussionmentioning
confidence: 94%
“…This greater reduction in virulence may stem from the SpGH92-mediated trimming of α-1,2 linkages from high-mannose-containing N -glycans being a prerequisite for the release of N -glycans by EndoD (Figure A) . Similarly, deletion of the gene encoding GH92 in Streptococcus suis SS2 revealed its contribution to virulence, supporting a general role for N -glycan processing as a virulence mechanism in pathogenic streptococci, a large proportion of which possess genes encoding GH92 enzymes . Accordingly, small-molecule inhibitors of SpGH92 may ultimately serve to deliver antivirulence therapeutics that target S. pneumoniae and possibly other streptococci.…”
Section: Introductionmentioning
confidence: 91%